Translating feminism - Schulz, Kristina (Cham: Palgrave Macmillan, 2021)
This edited book addresses the diversity across time and space of the sites, actors and practices of feminist translation from 1945-2000. The contributors examine what happens when a politically motivated text is translated linguistically and culturally, the translators and their aims, and the strategies employed when adapting texts to locally resonating discourses. The collection aims to answer these questions through case studies and a conceptual rethinking of the process of politically engaged translation, considering not only trained translators and publishers, but also feminist activists and groups, NGOs and writers. The book will be of interest to students and researchers in the fields of translation studies, gender/women's studies, literature and feminist history.
Keywords: Feminism; translation; Materiality of texts; Bookshops